Changing patterns of work at older ages - Rowena Crawford; Jonathan Cribb; Heidi Karjalainen; Laurence O'Brien (Institute for Fiscal Studies (IFS), 2021)
Longer working lives offer many benefits, but achieving these can pose challenges for individuals, employers and policymakers. In order to support people in their 50s and 60sto remain in paid work for longer, it is imperative that we have a good picture of what paid work looks like at older ages, and how that might evolve in future. The desired working patterns of older workers-in terms of their hours of work, the form of their employment or the tasks they undertake at work -may be quite different from those of middle-aged or younger adults. An ageing population and higher employment rates for people in their 50s and 60s mean that patterns of work of older workers are an increasingly important issue for the country as a whole. Indeed, in 2019, around 10millionor 61% of 50-to 69-year-olds were in paid work, meaning that this age group comprises almost a third (31%) of the workforce in the UK, up from just 21%in 1992. In this report, we provide fresh evidence on the nature of paid work at older ages, how employment patterns differ for people in different circumstances and how the situation is changing over time. In particular, we examine in depth the transitions that older workersmake, both intoand out of work and between different types of employment in the run-up to retirement.
Keywords: 330; Ältere Arbeitskräfte; Altersgrenze; Arbeitsuche; Teilzeitarbeit; Berufswechsel; Selbstständige; Großbritannien